TV Viewing, Perceived Similarity, Coviewing, and Mental Well-Being Among African American, Latino, and White Children. (April 2015) - McDade-Montez, Elizabeth; Wallander, Jan; Elliott, Marc; Grunbaum, Jo Anne; Tortolero, Susan; Cuccaro, Paula; Schuster, Mark A.
Research among adults has demonstrated concurrent and prospective negative associations between TV viewing and mental health, yet little research has examined these associations among African American and Latino youth or examined the role of children's involvement with TV and parental mediation of TV viewing via coviewing. The purpose of the present study is to examine associations between TV viewing, perceived similarity, and coviewing and mental well-being in African American, Latino, and White children. Results from Healthy Passages™, a study of 4, 824 African American (30%), Latino (47%), and White (23%) fifth graders, indicated that TV viewing and perceived similarity were negatively associated with mental well-being among most groups of children, and coviewing was positively associated with mental well-being among Latinos. This study extends findings from adult research on media exposure and mental well-being into a diverse sample of fifth graders and illuminates the role of perceived similarity and coviewing.